Bulletin of the American Museum of Natural History. - Allen, J. A.; American Museum of Natural History (New York [American Museum of Natural History], 1930)
Comprises articles on geology, paleontology, mammalogy, ornithology, entomology and anthropology.
Editor: 1889- J.A. Allen.
Issues published June 29, 1989-<Sept. 7, 2004> called: No. 189-<no. 286>.
Beginning with v. 23, information on anthropological matter continued in: Anthropological papers of the American Museum of Natural History.
SERBIB/SERLOC merged record
Keywords: Pássaros